Effect of different pollen grains on life table parameters of Neoseiulus barkeri (Acari: Phytoseiidae) - Maryam Rezaie; Sepideh Askarieh (Persian Journal of Acarology)
The predatory mite, Neoseiulus barkeri Hughes is one of the most important phytoseiid mites to control phytophagous mites. The effect of different diets such as, corn pollen, walnut pollen, sunflower pollen, date pollen, bee pollen along with the two-spotted spider mite (Tetranychus urticae Koch) eggs on life table parameters of the predatory mite was determined on strawberry detached leaves in Petri dishes. The experiments were carried out under laboratory conditions at 27 ± 1°C, 16L: 8D h photo-period and 70 ± 5% RH. The individuals of  the predatory mite were collected from cucumber field infested with the two-spotted spider mite of Khoramabad, Lorestan Province. The results indicated that mean preimaginal developmental time was the highest on sunflower pollen and bee pollen than the preimaginal developmental time on the other tested pollens. The developmental time of adult of  N. barkeri when fed with bee pollen (10.0 and 9.25 days for female and male, respectively) is longer than when it fed on the other diets. The fecundity rate of predatory mite on different diets did not show any significant difference. The intrinsic rate of increase (r) of the predatory mites fed with sunflower pollen (0.212 d-1), date pollen (0.225 d-1) and corn pollen (0.224 d-1) were higher than the other treatments. With attention to observed results, corn pollen, sunflower pollen and date pollen were suitable alternative food for the mass rearing of this predator.